USM OUTLINES FOUR MEASURES IN FACING CHALLENGES - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 30 April 2016 – The ViceChancellor of Universiti Sains Malaysia (USM), Professor Dato’ Dr. Omar Osman has outlined four measures for the university to implement in its operations, in order to face the challenges and constraints as it moves forward into the future.